2002
DOI: 10.1113/jphysiol.2001.013847
|View full text |Cite
|
Sign up to set email alerts
|

Rat nicotinic ACh receptor α7 and β2 subunits co‐assemble to form functional heteromeric nicotinic receptor channels

Abstract: Rat hippocampal interneurons express diverse subtypes of functional nicotinic acetylcholine receptors (nAChRs), including α7‐containing receptors that have properties unlike those expected for homomeric α7 nAChRs. We previously reported a strong correlation between expression of the α7 and of the β2 subunits in individual neurons. To explore whether co‐assembly of the α7 and β2 subunits might occur, these subunits were co‐expressed in Xenopus oocytes and the functional properties of heterologously expressed nA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(162 citation statements)
references
References 39 publications
7
154
0
1
Order By: Relevance
“…Recent data have demonstrated that heteromeric assembly of recombinant a7 and b2 subunits could form functional receptors, displaying some pharmacological differences with homomeric ones (Azam et al, 2003;Khiroug et al, 2002). Given the high expression level of a7 and b2 subunits in the hippocampus, it was therefore of interest to Profile of SSR180711 at a7 nicotinic receptors B Biton et al test the activity and efficacy of SSR180711 at native a7 nAChRs in cultured hippocampal neurons, possibly formed of a mixture of homomeric and heteromeric receptors (Azam et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data have demonstrated that heteromeric assembly of recombinant a7 and b2 subunits could form functional receptors, displaying some pharmacological differences with homomeric ones (Azam et al, 2003;Khiroug et al, 2002). Given the high expression level of a7 and b2 subunits in the hippocampus, it was therefore of interest to Profile of SSR180711 at a7 nicotinic receptors B Biton et al test the activity and efficacy of SSR180711 at native a7 nAChRs in cultured hippocampal neurons, possibly formed of a mixture of homomeric and heteromeric receptors (Azam et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is strong evidence that native a7 n-AChRs are homopentamers, some recent data suggest that rat a7 and b2 subunits can form functional heteromeric receptors (Khiroug et al, 2002). In addition, an homomeric a7 nAChR variant called a7-2 has been described to be expressed in some peripheral and central neurons, displaying a-BTX sensitivity and an slower rate of desensitization (Severance and Cuevas, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These receptors desensitize with 10-fold slower time constants ( Ϸ 200ϩ ms), which implies that other factors must regulate this process. Association with other subunits may partially explain this behavior: coexpression of ␤2 and ␣7 in oocytes slows the onset of desensitization twofold (Khiroug et al, 2002). Alternatively, post-translational modification induced by phosphorylation of ␣7 subunits (Moss et al, 1996) could alter desensitization (Huganir and Greengard, 1990;Swope et al, 1992), although there is no evidence at present that phosphorylation alters the kinetics of desensitization of ␣7 subunit-containing receptors (Alkondon et al, 1994;Lui and Berg, 1999).…”
Section: Homomeric ␣-Receptorsmentioning
confidence: 99%
“…Heteromeric receptors containing the ␣7 and ␤2 gene products can be produced by heterologous coexpression, and the receptors have diminished rates of desensitization (Khiroug et al, 2002). Native receptors containing coassembled ␣7 and ␤2 subunits have not been described, but examples of slowly desensitizing native ␣7-nAChRs have been reported (Cuevas and Berg, 1998;Yu and Role, 1998;Cuevas et al, 2000).…”
Section: Synaptic Options On Neurons Presynaptic Sitesmentioning
confidence: 99%